2020
DOI: 10.21873/anticanres.14230
|View full text |Cite
|
Sign up to set email alerts
|

The Application of a Low-temperature Physical Plasma Device Operating Under Atmospheric Pressure Leads to the Production of Toxic NO2

Abstract: Background: Physical plasma is a mixture of reactive particles and electromagnetic radiation. Due to the antimicrobial, immunomodulatory, anti-inflammatory, wound-healing promoting, and antineoplastic effects of body tempered physical plasma under atmospheric pressure (cold atmospheric plasma: CAP), CAP therapy is increasingly becoming the focus of surgical and oncological disciplines. However, when applied in practice, a potential emission of harmful noxae such as toxic nitrogen oxides must be taken into acco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…For EMD, as for pharmacological agents, a concentration can be defined, and dose-dependent effects can be detected [ 72 , 73 ]. In CAP treatment, it is not possible to define a concentration (of reactive species, for example) because these species continue to react very rapidly and have very short half-lives [ 74 ]. The only practical specification is the treatment duration, which leads to reproducible treatment duration-dependent effects [ 38 , 75 ].…”
Section: Discussionmentioning
confidence: 99%
“…For EMD, as for pharmacological agents, a concentration can be defined, and dose-dependent effects can be detected [ 72 , 73 ]. In CAP treatment, it is not possible to define a concentration (of reactive species, for example) because these species continue to react very rapidly and have very short half-lives [ 74 ]. The only practical specification is the treatment duration, which leads to reproducible treatment duration-dependent effects [ 38 , 75 ].…”
Section: Discussionmentioning
confidence: 99%
“…No reported local or systemic side effects when the dose and timing of application (20-180" daily; 7-14 days of treatment) are respected. Despite the fact that one study demonstrates the production of ultraviolet light (UV) radiation and of NO2, and their dispersion in the environment is a consequence of CAP production, no pathologic sequelae were reported by the authors of the paper (18).…”
Section: Cold Atmospheric Plasmamentioning
confidence: 99%
“…Expression levels of HSP40 and BAG3 were significantly enhanced [96,131], suggesting that NIPP exposure expands ROS levels inhibiting NIPP-induced apoptosis. Previous studies have shown that nitric oxide (NO) is produced during NIPP treatment and rapidly converted to other ROS, including NOX [132,133]. NO induces HSF1-regulated HSP70 expression and subsequent cytoprotection [125,126,134].…”
Section: Hsp70mentioning
confidence: 99%